Sex, desire, and taboo in South Asia religion, culture of ability, and patriarchy - Acharya, Tulasi (Lanham Boulder New York London Lexington Books, 2024)
"Sex, Desire, and Taboo in South Asia investigates how religion, ability culture, patriarchy, and taboos impact sex and desire in South Asia. Through analysis of theories of sexuality alongside erotic literature, the book underscores the need for intersectional approaches when discussing taboos around the world"--
Theory on Sexuality -- Introduction to Sex and Erotica -- Discourse of Sex in South Asia -- Perception and Patriarchy -- Religion, Patriarchy and Gender -- Existing Research and Significance of Sex.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Sex -- South Asia; Sex customs -- South Asia; Taboo -- South Asia; Erotic literature -- South Asia